Analisis Efektivitas Program Ekstrakulikuler Dalam Pembentukkan Karakter Profil Pelajar Pancasila di SMPN 51 Bandung - Sukarno, Ulfan Arfandi; Nurdin, N; Suharto, Nugraha (Universitas Pendidikan Indonesia, 2024)
The Merdeka Curriculum is one of the efforts to answer the problems faced in Indonesian education. After the 2019 Covid Pandemic, there were many obstacles that made the process of receiving educational knowledge in schools not optimally accepted by students. This also affects the daily character of students, both at school and outside of school. The character of post-pandemic students seems not ready to accept learning as usual, therefore an adaptation is needed in the form of an approach for students so that they are ready to study at school again. This type of research is descriptive research with a qualitative approach. The research method that will be used is descriptive qualitative. The Pancasila Student Profile is part of the Merdeka Curriculum, various ways and approaches are applied by schools so that students become students with the character of the Pancasila Profile. One effort to achieve this is through extracurricullar programs. The extracurricullar program at junior high school 51 Bandung runs effectively for students. In addition, the character formation of the Pancasila Student Profile at junior high school 51 Bandung has also been going well where students' character is formed through the programs provided by the school. Based on the results of effectiveness analysis extracurricular program for building Pancasila Student Profile In junior high school 51 Bandung, it was found that Kijarpara as an extracurricular was successful in shaping the character of students, due to changes in students' character before and after attending Kijarpara. This achievement was also supported by various other related aspects, when analyzed and examined, turned out to be quite complex.